Impact of Klaipėda port jetties reconstruction on adjacent sea coast dynamics - Jarmalavičius, Darius; Žilinskas, Gintautas; Pupienis, Donatas (Journal of Environmental Engineering and Landscape Management, 2012)
During the reconstruction of 2001–2002, the Klaipėda port jetties were lengthened (the northern jetty by 205 m and the southern by 278 m). These works produced an impact on dynamic coastal processes in the neighbourhood of the port. The evaluation of the impact of jetties reconstruction was based on the data obtained in 1995–2010 during the monitoring of coastal dynamics in the port of Klaipėda. Study area includes 10 km coastal strip of mainland and 12 km coastal strip of Curonian Spit. The analysis of the data concerning the changes in the annual amount of coastal sediment served as a basis to evaluate the impact of Klaipėda port jetties on the trends in coastal dynamics prevailing before the reconstruction and their changes after it. It was found that in the mainland coastal stretch closest to the jetties, where in the last decade before jetties extension the seashore was relatively stable, the coastal erosion trends were dominant. Meanwhile, the closest to the jetties coastal stretch of the Curonion Spit, where erosion processes dominated in the last decade before jetties extension, stabilized right after the reconstruction and with a passage of time sediment accumulation trends have become prevailing.Article in English.Rekonstruotųjų Klaipėdos uosto molų įtaka gretimų jūros krantų dinamikaiSantrauka. 2001–2002 m. vykdant Klaipėdos jūrų uosto rekonstrukcijos darbus buvo prailginti molai (šiaurinis 205 m, pietinis – 278 m). Vertinant molų rekonstrukcijos įtaką jūros krantų greta uosto dinamikai remtasi nuo 1995 m. atliekamos jos stebėsenos duomenimis. Tyrimų rajonas apėmė 10 km ilgio žemyno kranto juostą ir 12 km ilgio Kuršių nerijos kranto juostą. Matavimai buvo atliekami 18 profilių žemyno krante ir 12 profilių Kuršių nerijos krante. Analizuojant kasmetinės kranto sąnašų kiekio kaitos duomenis įvertinta Klaipėdos uosto molų įtaka gretimų krantų dinamikos tendencijoms, vyravusioms iki molų rekonstrukcijos, ir jų pokyčiams po molų rekonstrukcijos. Nustatyta, kad žemyne, arčiausiai molų esančioje kranto atkarpoje, kurioje pastarąjį dešimtmetį iki uosto molų prailginimo krantas buvo santykinai stabilus, po rekonstrukcijos įsivyravo kranto ardos tendencijos. Kuršių nerijos krante, kur pastarąjį dešimtmetį iki molų prailginimo arčiausioje nuo molo kranto atkarpoje vyravo intensyviõs ardos procesai, po molų rekonstrukcijos krantas iš pradžių stabilizavosi, o vėliau čia pradėjo vyrauti sąnašų akumuliacijos tendencijos.Reikšminiai žodžiai: aplinkos stebėsena, Klaipėdos uostas, molai, kranto sąnašos, įplaukos kanalo pagilinimas